Предмет: Алгебра,
автор: yokeri
Алгебра. Помогите пожалуйста. 20 баллов.
Приложения:
Ответы
Автор ответа:
0
Ответ:
Объяснение:
((x+2)/(x-2) -x/(x+2))·(x-2)/(3x+2)=2/(x+2)
1) (x+2)/(x-2) -x/(x+2)=((x+2)²-x(x-2))/((x-2)(x+2))=(x²+4x+4-x²+2x)/((x-2)(x+2))=(6x+4)/((x-2)(x+2))=(2(3x+2))/((x-2)(x+2))
2) (2(3x+2))/((x-2)(x+2))·(x-2)/(3x+2)=2/(x+2)
((3x)/(4y³))³=(27x³)/(64y^(3·3))=(27x³)/(64y⁹)
Похожие вопросы
Предмет: Русский язык,
автор: AleshaPrutskov
Предмет: Русский язык,
автор: Аноним
Предмет: Русский язык,
автор: Jukmi
Предмет: Қазақ тiлi,
автор: akmaralzhakyp